How does maternal sensitivity during a child's infant and preschool years individually affect the child's emotional memory at the preschool level? - Lim, Charlene (Nanyang Technological University, 2023)
Introduction: The emotions that we experience during events would influence the memories that we encode and retrieve. Given that parents are children’s first teachers, it highlights the importance of a child’s interactions with their mothers, especially in their early years of life, on their overall development. This study sought to examine the impact of maternal sensitivity on children’s emotional memory. Methods: Mothers and their children were brought into a room to engage in developmentally appropriate activities and their interactions were recorded. Trained coders used versions of the MBQS to code for maternal sensitivity. This occurred at two timepoints – infancy (when the child was approximately 6 months old) and preschool (when the child was between 4- to 6-years-old). Emotional memory was measured using a Relational Memory Binding Task which had two emotional conditions (happy and angry) and three memory conditions (Item Time, Item-Item, and Item-Space). Prediction: Better memory performance for angry stimuli than happy stimuli. Maternal sensitivity measured at both timepoints affects emotional memory. Potential sensitive periods are explored by comparing the predicting value of each timepoint. Results: Memory for the happy and angry stimuli did not significantly differ for all children. Of the three memory conditions, only the Space condition demonstrated significantly poorer performance. For early life caregiving, maternal sensitivity at neither the infant nor preschool timepoints predicted preschool emotional memory. There was no comparison of sensitive periods to speak of. Discussion: Findings are only partially supported by extant literature. Limitations and directions for future research are discussed.